Achievements of Tibetan medicine and their reflection in Kalmyk Buddhist medical terminology: Tibetan-Oirat parallels, their semantics and etymology (based on written sources on the “Clear writing” and their russian translations) - E. U. Omakaeva (Nomadic Civilization: Historical Research, 2024)
This article is devoted to the study of the Kalmyk branch of Tibetan medicine — a practically little-studied object of research. This topic was usually considered from a historical and cultural perspective. Meanwhile, the terminology of this subject area is of particular research interest, deserving a holistic description of its various components. The main task is to pose the problem of constructing a Tibetan-Kalmyk-Russian thesaurus of traditional medical terminology, which requires a comprehensive study and systematization of key terms denoting generic objects of research, as well as sections and related disciplines of the subject area “Buddhist Medicine”. Terms are considered through the prism of cluster field approaches, lexical-semantic classification (groups and subgroups) and the linguistic worldview. Research into Buddhist medical vocabulary and terminology is untenable without a deep study of Buddhism itself as a multidimensional phenomenon and a medical fragment of the linguistic picture of the world as the intersection point of two most important sign systems — religion and the language that serves it. The author briefly presents the history of the spread of Tibetan medicine among the Kalmyks, shows the role of the expert on Tibetan medicine Dambo Ulyanov in its study, and his activities in translating the medical treatise “Zhud-shi” into Russian.